I see you, you see me: the impact of social presence on social interaction processes in autistic and non-autistic people. (24th April 2023) - Freeth, Megan; Morgan, Emma J.
Abstract : Environments that require social interaction are complex, challenging and sometimes experienced as overwhelming by autistic people. However, all too often theories relating to social interaction processes are created, and interventions are proposed, on the basis of data collected from studies that do not involve genuine social encounters nor do they consider the perception of social presence to be a potentially influential factor. In this review, we begin by considering why face-to-face interaction research is important in this field. We then discuss how the perception of social agency and social presence can influence conclusions about social interaction processes. We then outline some insights gained from face-to-face interaction research conducted with both autistic and non-autistic people. We finish by considering the impact of social presence on cognitive processes more broadly, including theory of mind. Overall, we demonstrate that choice of stimuli in studies assessing social interaction processes has the potential to substantially alter conclusions drawn. Ecological validity matters and social presence, in particular, is a critical factor that fundamentally impacts social interaction processes in both autistic and non-autistic people. This article is part of a discussion meeting issue 'Face2face: advancing the science of social interaction'.